Retreival Strategies in Students' Analogical Thinking Processes in Geometry Problem Solving - Yunita Setiyaningsih; Yulia Maftuhah Hidayati (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze the retrieval strategies used by elementary school students in the process of analogical thinking when solving geometry problems. This study specifically focuses on how students retrieve prior knowledge as a basis for forming analogies in the context of solving geometry problems. Methodology: This study used a descriptive qualitative approach with 24 sixth-grade students from SDN 2 Kemasan as subjects. Data were collected through geometry problem-solving tests, semi-structured interviews, and documentation, then analyzed using Miles and Huberman's interactive model, which includes data reduction, data presentation, and conclusion drawing.Results: The results showed that there were three main strategies used by students in retrieval, namely: (1) spontaneously remembering formulas or properties of flat shapes, (2) drawing flat shapes as a trigger for visual memory, and (3) relating problems to concrete everyday experiences. These strategies indicate that retrieval does not occur in isolation but is influenced by the strength of memory, learning experiences, and the thinking styles of each student. Applications/Originality/Value: The novelty of this study lies in the retrieval stage in analogical reasoning, which has not been widely studied in previous studies. This study analyzes the retrieval strategies used by students, thereby providing new insights into how memory works in solving geometry problems.